5 Gender disparities in aortic stenosis: an optimised assessment using contrast-enhanced computed tomography. (May 2018) - Cartlidge, Timothy RG; Pawade, Tania A; Doris, Mhairi K; Kwiecinski, Jacek; White, Audrey C; D Gray, Calum; Adamson, Philip A; Newby, David E; Dweck, Marc R
Abstract : Introduction: Non-contrast CT aortic valve calcium scoring (AVC) provides assessment of disease severity in aortic stenosis (AS). However, gender differences in the pathogenesis of AS are apparent. Contrast-enhanced CT has the potential to assess both valve calcification and fibrosis but to date has been relatively unexplored. Methods: Volunteers (39 mild, 78 moderate, 26 severe AS; 20% female) underwent echocardiography, non-contrast and contrast-enhanced CT. AVC was measured on non-contrast CT. Contrast-enhanced CT was used to quantify volumes of calcium and non-calcific valve thickening (fibrosis). Results: Contrast-enhanced CT calcium volumes correlated closely with AVC (r=0.86, p<0.001), and with peak velocity on echocardiography (r=0.57, p<0.001). Clear gender differences were apparent in the contrast-enhanced CT assessment. Males displayed higher calcium volumes than females, even after correction for annulus area (p<0.001). There was a striking difference in the calcium:fibrosis ratio with males having proportionally more calcium than fibrosis and females showing the reverse (males: 1.17 [0.67–2.25] versus females: 0.56 [0.09–1.22], p<0.001). In men, calcium volumes displayed a moderate correlation with peak velocity (r=0.58, p<0.001) whereas in women there was no significant association (r=0.33, p=0.086). Fibrosis volumes demonstrated a weak correlation with peak velocity in men (r=0.26, p=0.006) which was notably stronger in women (r=0.43, p=0.02). A composite fibro-calcific volume provided the strongest correlation with peak velocity in both groups (men: r=0.63, p<0.001; women: r=0.64, p<0.001). Conclusion: Contrast-enhanced CT can be used to quantify calcific and fibrotic valve thickening in AS and may be able to address gender discrepancies in the assessment of disease severity.